La responsabilidad objetiva del estado frente a la acción del derecho de repetición - Cumbicus Soto, María Fernanda (2019)
This research work has the purpose of carrying out a study regarding the Objective Responsibility of the State against the constitutional right of the State to exercise the Repeat Action against public servants who, in the exercise of their functions, will cause damage or harm to the private individuals. The research is carried out through an analytical study, addressing the research from a technical-legal approach, the procedural aspects of the State's responsibility and its right to exercise the repetition action, in order to determine the existing legal problems and gaps in the applicable procedures…………